Implementation of Virtual Classroom and Zoom Networks in Continuing Student Learning - Nurbaiti Nurbaiti; Nadhrah Al Aflah; Supardi Supardi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Almost all corners of the world have been affected or affected by this Covid-19 virus disease, even some countries have set a lockdown status and other anticipations for the spread of the Covid-19 virus. The alternative used in this bold learning activity system is to utilize the internet network, namely the Zoom Meeting and Classroom application. This study aims to determine students' perceptions of the use of internet networks such as zoom meetings and classrooms used and how effective learning is during the Covid-19 pandemic. The research conducted here uses descriptive qualitative research methods. And the results of this study indicate that the zoom application is an application that is very effective and preferred by students because it is easier to use and very efficient when the learning process is bold and shows that some students who give their perception of the application used during learning that are brave are the Zoom Meeting application, namely the application. Zoom Meeting. by 66.7%, followed by the Google Meet application at 22.2% and the Classrom application at 11.1%.